08 - LOW BACK PAIN AND LUMBOSCIATIC PAIN - COMPARATIVE STUDY OF SYSTEMIC TREATMENT WITH ACUPUNCTURE AND AURICULAR ACUPUNCTURE (Fiep Bulletin - online, 2011)
The low back pain is one of the most common complaints reported by patients, usually associated with poor posture, obesity, trauma, inflammatory, infectious or neoplastic changes bone, muscle and disc injury. Bibliographical evidence shows that the use of Acupuncture is efficient, especially in the treatment of chronic low back pain. In order to compare the use of Systemic Acupuncture and Auricular Acupuncture Systemic in cases of low back pain and this type of work Experimental Clinical Trial, included 10 volunteers aged between 25 and 60 years, of both sexes, randomly selected from two groups with 5 subjects each. The Group A which was conducted Systemic Acupuncture group B and Auricular Acupuncture. The assessment of the before and after was made following the parameters of the Visual Analogue Scale (VAS). The average grade given to the initial VAS pain in the group treated with Systemic Acupuncture therapy was 7.6 (± 0.54), from the end of treatment, 2.4 (± 0.54), with improvement of 70 %. In the Auricular Acupuncture group, the average initial pain score given was 8.6 (± 1.14) passing, after treatment, 2.8 (± 0.83) with improvement of 67%. Through these processing techniques can verify the reductions in pain scores that show the benefit of acupuncture, given the small difference between the groups surveyed.
Keywords: Auricular Acupuncture; Systemic Acupuncture; Low Back Pain